Stephen Dedalus as a Mythical Hero: Retelling Myths in Joyce’s A Portrait of the Artist as a Young Man - Sharma, Prakash (The Outlook: Journal of English Studies, 2024)
This paper explores the reappearance of Stephen Dedalus as a mythical hero in modern form as reflected in James Joyce’s novel A Portrait of the Artist as a Young Man using the critical insights of myth critics. This exploration aims to reveal the universality of myth. It claims that in the novel the mythical hero, Daedalus, is revealed as Stephan Dedalus. Stephen’s journey from childhood to maturity with epiphany and transformation resembles the journey of the mythical hero. His struggles to escape from the trap of religion, family, and nationality to be an artist are similar to the struggles of the mythical hero, Daedalus. More specifically, Stephan's psychological development towards a critical understanding of his own society echoes Daedalus' skill development of making wings of feathers and wax. Similarly, Stephen’s motive for escaping to Paris reflects Daedalus’s realization of the urgency of moving to Sicily. This study uses qualitative research design and method of textual analysis to locate the resurfacing of mythical ideas in modern context. Textual data taken from the primary text are analyzed using the theoretical insights of Joseph Campbell and other myth critics, in relation to the ideas of the universality of myth and the role of hero, to explore the issue.